Stretching the structural envelope of imatinib to reduce β-amyloid production by modulating both β- and γ-secretase cleavages of APP - Netzer, William J.; Sinha, Anjana; Ghias, Mondana; Chang, Emily; Gindinova, Katherina; Mui, Emily; Seo, Ji-Seon; Sinha, Subhash C. (Frontiers in Chemistry, 2024)
We previously showed that the anticancer drug imatinib mesylate (IMT, trade name: Gleevec) and a chemically distinct compound, DV2-103 (a kinase-inactive derivative of the potent Abl and Src kinase inhibitor, PD173955) lower Aβ levels at low micromolar concentrations primarily through a lysosome-dependent mechanism that renders APP less susceptible to proteolysis by BACE1 without directly inhibiting BACE1 enzymatic activity, or broadly inhibiting the processing of other BACE1 substrates. Additionally, IMT indirectly inhibits γ-secretase and stimulates autophagy, and thus may decrease Aβ levels through multiple pathways. In two recent studies we demonstrated similar effects on APP metabolism caused by derivatives of IMT and DV2-103. In the present study, we synthesized and tested radically altered IMT isomers (IMTi’s) that possess medium structural similarity to IMT. Independent of structural similarity, these isomers manifest widely differing potencies in altering APP metabolism. These will enable us to choose the most potent isomers for further derivatization.